1976
DOI: 10.1111/j.1365-2362.1976.tb00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin II and Noradrenaline on Intrarenal Haemodynamies in the Rat*

Abstract: The haemodynamic effects of angiotensin II and noradrenaline were studied in the rat kidney. These pressors were given by intravenous infusion in stepwise increasing doses. Intrarenal haemodynamics were analyzed by the 133xenon washout technique, 85krypton autoradiography and silastic casting of the renal vascular tree. Angiotensin II induced significant changes in intrarenal haemodynamics before any changes in systemic blood pressure were detected. The decrease in mean renal blood flow (2.91 ml.min-1.g-1 in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…distribution similar to that found by others [4,13] using 133Xe in rats though our flow rates to compartments I and 11 are slightly lower. Our mean flow index for N rats is within the range found by others using l33Xe in rats [4.13.14] but is slightly lower than that obtained by 8(iRb methods [6,15] and microspheres [16,17], The problems and limitations in interpretation of inert gas washout data have been discussed by other workers [5.6,8], We have limited our study to a comparison be tween two groups of animals under similar conditions and have shown that there is a difference in renal haemody namics between GH and N rats under the conditions of our study.…”
Section: Discussionsupporting
confidence: 75%
“…distribution similar to that found by others [4,13] using 133Xe in rats though our flow rates to compartments I and 11 are slightly lower. Our mean flow index for N rats is within the range found by others using l33Xe in rats [4.13.14] but is slightly lower than that obtained by 8(iRb methods [6,15] and microspheres [16,17], The problems and limitations in interpretation of inert gas washout data have been discussed by other workers [5.6,8], We have limited our study to a comparison be tween two groups of animals under similar conditions and have shown that there is a difference in renal haemody namics between GH and N rats under the conditions of our study.…”
Section: Discussionsupporting
confidence: 75%
“…(1) AT-I1 selectively increased tumor blood flow (Suzuki et al, 1981) and consequently delivery of CDDP to the tumor; and (2) transient inhibition of CDDP delivery to the kidney occurred during AT-11-induced hypertension, as AT-I1 decreases renal blood flow (Rentsch et al, 1976;Tvete et al, 1981), so that post-administration of STS to CDDP became feasible.…”
mentioning
confidence: 99%
“…In many instances it has been difficult to attribute the observed changes directly to the experimental conditions and to separate them from effects mediated by variations in per fusion pressure [21,22].…”
mentioning
confidence: 99%